PEMETAAN BUDAYA ORGANISASI PERAWAT DENGAN PENDEKATAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT DI RS MOH. RIDWAN MEURAKSA JAKARTA - Clarissa Carera (2023)
Organizational culture is a value or belief that an organization has as a guideline for behavior. Besides being useful for increasing patient satisfaction, organizational culture can also affect the quality of nurse's performance in implementing their roles. This study aims to analyze the maping of nurse's organizational culture with organizational culture assessment instrument approach in Moh. Ridwan Meuraksa Jakarta Hospital. This research method is descriptive analytic with corss sectional approach, using total sampling technique in collecting the data of 108 respondents. Data were analyzed using Google Spreadsheet. The results showed that the current organizational culture at Moh. Ridwan Meuraksa Jakarta Hospital is dominant at Adhocracy and Market culture (26.29%). Meanwhile, the preferred culture is Clan culture with mean percentage of 28.26%. In conclusion, the nurse preferred an organizational culture which is family-oriented with high loyalty and commitment and focused on internal factors in the organization. Therefore, the hospital management is expected to increase the opportunity of nurses development by conducting training, seminar and socialization, and giving education fund for nurses who desire to continue their education level. Keywords: Organizational Culture, Organizational Culture Assessment Instrument, Nurse